Diversifying University Income Models Beyond Academic Revenue: Governance, Risk Perception and Comparative Insights - Sari, Anggi Mayang; Indrawan, Dikky; Abdullah, Asaduddin; Zuna, Muhammad Alwanrifqi (Business Review and Case Studies, 2025)
Background: Declining public funding, intensified competition, and changing student demographics have forced universities worldwide to seek alternative income sources beyond tuition fees, research grants, and government support.Purpose: This study aims to identify and evaluate contemporary non-academic income models in higher education institutions through Resource-Based View (RBV) and the entrepreneurial university framework, with a focus on governance capacity and risk perception in strategic decision-making. The analysis explores strategies, enablers, and constraints shaping the diversification of university income streams across different institutional contexts.Design/methodology/approach: A descriptive qualitative approach with content analysis was applied, examining secondary data from 50 universities across five continents, selected based on data availability, institutional ranking, and regional representation. Data sources included institutional reports, audited financial statements, global ranking databases, and peer-reviewed literature. Findings/Result: Institutions with strong governance systems and higher strategic risk tolerance are better positioned to leverage unique assets such as large endowments, intellectual property portfolios, and real estate holdings for substantial revenue generation. Other institutions rely more on faculty expertise, sectoral partnerships, and philanthropic innovations to fund scholarships, research, and infrastructure development. Conclusion: Key success factors are asset uniqueness, governance capacity, and market alignment, while challenges include regulation, mission drift, and limited resources. The study suggests universities enhance governance autonomy, establish professional asset and IP management, and align diversification with institutional missions. Resource-constrained institutions should prioritize partnerships, community-based revenue, and transparent financial management to build trust. Financially mature institutions should expand sustainable investments and leverage global alumni networks to strengthen resilience.Originality/value (State of the art): This research contributes to the discourse on financial sustainability in higher education by integrating governance and risk perception into the analysis of non-academic income diversification that address capacity gaps and market opportunities across diverse institutional settings.Keywords: behavioral finance, business models, entrepreneurial university, financial sustainability, governance, non-academic revenue, risk perception